DIGITAL ECONOMY – AN ELEMENT OF INFORMATION (Farabi Journal of Social Sciences, 2020)
Over the past decades, the world has been rapidly moving towards a new type of economy, where digitaltechnologies are becoming the main tool for its formation. Expanding the role of information technology in the privateand public sectors is the basis for the transition to a digital state.The term «digital economy» (digitaleconomy) was first used relatively recently, in 1995, by an Americanscientist from the University of Massachusetts, Nicholas Negroponte, to explain to colleagues the advantages ofthe new economy in comparison with the old one in connection with the intensive development of information andcommunication technologies. The article deals with the concept of the digital economy, its introduction, and the worldexperience of structural and institutional support for the development of the digital economy. Special attention ispaid to the development and implementation of digital technologies in the economy. Based on the studied material, itwas concluded that for the application of modern technologies in all sectors of human life, it is necessary to developappropriate programs that ensure the effective use of digital technologies.